The Struggle of Memory against Forgetting in Lois Lowry’s The Giver, Yoko Ogawa’s The Memory Police, and Kazuo Ishiguro’s The Buried Giant - Kaiissar, Jahin (Brac University, 2021)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2021.